Radiological Diagnosis in Lung Disease: Factoring Treatment Options Into the Choice of Diagnostic Modality - Wielpütz, Mark O (Deutscher Arzte Verlag, 2014)
BACKGROUND: Chest X-ray, computed tomography (CT), and magnetic resonance imaging (MRI) each have characteristic advantages and disadvantages that need to be considered in clinical decision-making. This point is discussed in reference to the main types of lung disease that are encountered in practice. METHODS: A selective literature search was performed in the PubMed and Google Scholar databases. Existing clinical guidelines on the main types of lung disease and studies concerning radiological diagnosis were also considered in this review. RESULTS: There have been no more than a few large-scale, controlled comparative trials of different radiological techniques. Chest X-ray provides general orientation as an initial diagnostic study and is especially useful in the diagnosis of pneumonia, cancer, and chronic obstructive pulmonary disease (COPD). Multi-detector CT affords nearly isotropic spatial resolution at a radiation dose of only 0.2–5 mSv, much lower than before. Its main indications, according to current guidelines, are tumors, acute pulmonary embolism, pulmonary hypertension, pulmonary fibrosis, advanced COPD, and pneumonia in a high-risk patient. MRI is used in the diagnosis of cystic fibrosis, pulmonary embolism, pulmonary hypertension, and bronchial carcinoma. The positive predictive value (PPV) of a chest X-ray in outpatients with pneumonia is only 27% (gold standard, CT); in contrast, an initial, non-randomized trial of MRI in nosocomial pneumonia revealed a PPV of 95%. For the staging of mediastinal lymph nodes in bronchial carcinoma, MRI has a PPV of 88% and positron emission tomography with CT (PET/CT) has a PPV of 79%, while CT alone has a PPV of 41% (gold standard, histology). CONCLUSION: The choice of radiologicalal technique for the detection, staging, follow-up, and quantification of lung disease should be based on the individual clinical options, so that appropriate treatment can be provided without excessive use of diagnostic testing.